MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BOLA BASKET SISWA KELAS VIII SMP N 7 SINGARAJA - Gede Hendri Ari Susila; Kadek Suardika; Ketut Agus Artha (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2019)
This research aims to improve activity and learning outcomes basketball passing (chest pass and bounce pass) trough the implementation cooperative learning model type numbered head together (NHT) on student class VIII SMP N 7 Singaraja school year 2017/2018. This study is an class action researchers wich is conducted in two cycles, consist of action planning stage, implementation of the action, observation/evaluation and reflection. Research subject is student of class VIII SMP N 7 Singaraja which amounts 38 persons consist of 26 men and 12 women. Data were analyzed using descriptive statistical analysis. Learnig activity data in cycle 1 classically is 7,98 and learning research of cycle 1 achieve 52% in the category of fairly good. Learning activity data in cycle classically is 9,3 and learning research of cycle achieve 100% in the category of very good. Bused on analysisdata result and discussion, concluded that activity of learning outcomes basketball passing techniques increased through the application of cooperative learning model type (NHT) for student in class VIII SMP N 7 Singaraja school year 2017/2018. Adviced on penjasorkes (spot) teachers can apply cooperative learning outcomes basketball passing techniques.